The Relationshipbetween EU Law and National Constitutional Law in the Field of Fundamental Rights - S.G. Barbu; C.M. Florescu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The Constitutional Court of Romania carries out the control of the constitutionality of the laws and ordinances of the government and pronounces decisions that have a binding effect erga omnes. Within the constitutionality control, a special position is occupied by the EU law. In our paper we will focus on the interferences that may arise between the national norm, the EU law and the national Constitution, from the perspective of the jurisprudence of the Constitutional Court and the principle of priority of the EU law.